Strategi Positioning dan Citra Merek Pixy Lipcream dalam Mempengaruhi Keputusan Pembelian: Survei pada Mahasiswi Manajemen Universitas Perjuangan Tasikmalaya - Stephanie Graciana (CV. Ulil Albab Corp, 2022)
This study aims to determine the positioning strategy and brand image of Pixy Lipcream Products in influencing purchase decisions (Survey of Management Study at Universitas Perjuangan Tasikmalaya). The research method used is the casual method with a Research sample of 100 respondents and the analytical tol used in this study is multiple linear regression using SPSS version 25. Based on the results of the Study, it is known that positioning strategy and brand image have a significant simultaneous effect on Pixy Lipcream purchase decisions. Positioning strategy has a significant effect partially on the purchase decision of Pixy Lipcream. Brand image has a significant effect partially on the purchase decision of Pixy Lipcream.